Testing explosive strength and speed in endurance athletes may help to improve the performance in running events
The performance in endurance event (running events especially) is based on the VO2max, lactate threshold and running economy (economy of locomotion for example skiing). However, endurance performance is not solely related to oxygen transport and use. Several neuromuscular factors of force production ability also play a very important role: muscle contractility, ability to utilize the potential energy stored in muscle structures during the pre-stretch of the run cycle i.e. the stretch-shortening cycle (SSC), force-time characteristics of the muscles. These characteristics can be improved significantly with explosive type strength training in endurance athletes as in power athletes. These improvements may, then, be transferred to other performance factors such as improved (shortened) ground contact time, improved anaerobic energy production, improved force production during the running gait cycle leading into improved running economy. The speed training is shown to improve the submaximal movement (running) velocity and running economy, which in turn also helps in improving the endurance performance. According to Di Pampero et al., 1993) a 5% decrease in the energy cost of running results in 3.8% improvement in distance running time. An example: an athlete`s time in 5000-m race is 13.47, after the training and improved running economy the improvement may be as significant as 31.43 s with time improved to 12.96!